Pseudomyxoma peritonei with intrathoracic extension: a rare disease with rarer presentation from low-grade mucinous adenocarcinoma of the appendix. (4th January 2016) - Ghosh, Raktim K; Somasundaram, Mey; Ravakhah, Keyvan; Hassan, Chandra
Abstract : Pseudomyxoma peritonei is an extremely rare disease, characterised by mucinous ascites and implants, diffusely involving the peritoneal surfaces. Recent pathological and genetic advances indicate that they mostly originate from an appendiceal adenoma or adenocarcinoma. The successful treatment of peritoneal carcinomatosis requires a comprehensive management plan including cytoreductive surgery, intraoperative intraperitoneal heated chemotherapy and postoperative systemic chemotherapy. It is extremely rare to have intrathoracic spread of the disease at initial presentation. Some of the possible hypotheses of neoplastic cells spreading into the pleural cavity include congenital or acquired pleura-peritoneal communications, invasion of lymphovascular space and, rarely, through direct invasion of the diaphragm.